Electric Car Purchase Interest Analysis: Price and Purchasing Power Moderated by Government Policy in Bogor - Setio, Kiki; Adji, Askardiya R. (EAJ (Economic and Accounting Journal), 2026)
Price, purchasing power and government policy are three of several factors that are thought to be relatively strong in influencing the interest in buying electric cars. To prove the influence of the three, it is necessary to conduct research with the aim of determining the influence between the variables Price, purchasing power on purchasing interest with government policy as a moderating variable. This research was conducted in the Bogor city community with a sample of 97 respondents, the formula used to calculate it is Lamesshow. Data collection was carried out using questionnaires distributed offline and online. Data was processed using Partial Least Square (PLS-SEM), which is one of the Structural Equation Modeling (SEM) techniques that is able to analyze latent variables, indicator variables and measurement errors. The results show that price and purchasing power influence purchasing interest, government policy moderates the influence between price on purchasing interest, while government policy does not moderate the influence between purchasing power on purchasing interest. based on the results of this study, it shows that all variables influence purchasing interest, even government policy can moderate the relationship between price and purchasing interest, but government policy does not moderate purchasing power on purchasing interest.